2012
DOI: 10.1175/jas-d-11-0198.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivities of Orographic Precipitation to Terrain Geometry and Upstream Conditions in Idealized Simulations

Abstract: This study examines how variations in relatively simple terrain geometries influence orographic precipitation and its spatial patterns of sensitivity to small changes in upstream conditions. An idealized threedimensional model is used to simulate a moist flow impinging upon three alpine-scale terrain shapes: a straight ridge, a concave ridge, and a convex ridge. A variety of simulations are conducted to investigate the sensitivity of precipitation patterns to ridge length and upstream thermodynamic and wind co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…These results are in agreement with those of Watson and Lane (2012) who showed that in a linear regime, i.e. Nh/u <<1, there is limited sensitivity of terrain-induced flows to upstream wind direction because small changes do not cause a regime transition.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with those of Watson and Lane (2012) who showed that in a linear regime, i.e. Nh/u <<1, there is limited sensitivity of terrain-induced flows to upstream wind direction because small changes do not cause a regime transition.…”
Section: Discussionsupporting
confidence: 93%
“…This funneling is similar to that produced by concave ridges (Schneidereit and Sch€ ar 2000;Gheusi and Davies 2004;Jiang 2006;Watson and Lane 2012) and strongly enhances the precipitation downstream of the GSL. Latent heating from condensation and fusion likely serves as an additional nonlinear feedback mechanism for enhancing the crossband circulation and precipitation during the event.…”
Section: Discussionmentioning
confidence: 63%
“…Mountain ranges farther to the west (i.e., the Stansbury and Cedar Mountains) broaden the horizontal scale of the discontinuous concavity. In idealized simulations, Watson and Lane (2012) show that outer portions of a concave ridge deflect flow inward to yield flow deceleration, convergence, and enhanced upward motions. A comparison of the low-level flows in WAS and DT supports this conceptual model.…”
Section: E Downstream Orographic Influencesmentioning
confidence: 98%
See 1 more Smart Citation
“…Cannon et al (2012) found from idealized numerical simulations that embedded convection over tall and wide mountains causes competing effects (enhanced condensation in updrafts and enhanced evaporation through turbulent mixing and compensating subsidence) and leads to little net change in precipitation, while, for short and narrow mountains, convective updrafts strongly enhance the precipitation efficiency. Watson andLane (2012, 2014) undertook idealized, highresolution simulations and found that a concave ridge generates substantially more precipitation than the straight and convex ridges. A number of real-world simulations have focused on the island of Hawaii (e.g., Rasmussen et al 1989;Reisner and Smolarkiewicz 1994), where the 4-km mountain peak is found to create blocking with a large nondimensional mountain height.…”
mentioning
confidence: 99%